Exploratory Studies On Drug Abuse In The Asian Region-1996. - Navaratnam, V. (Pusat Penyelidikan Dadah dan Ubat-Ubatan Universiti Sains Malaysia, 1997)
A study was undertaken to understand the nature and trend of buprenorphine abuse on the basis of users response. A snowball sample 0£30 individuals who had been using buprenorphine for different durations were included .in this ethnographic study.